Interaction of Higher School and Employers on Training of Management Personnel in Digital Society (According to Materials of Mass Media and Social Media) - Zakharova, S.A.; Yudina, E.N. (KnE Social Sciences, 2021)
This article is devoted to the requirements that digital society proposes to educational organizations and employers. Educational organizations should improve the specialists’ and employers’ training quality as well as their participation in the evaluation of educational programs. Ensuring the quality of education is a task of all actors in the education system such as educational organizations, students, their parents, and employers. The authors carried out a study to determine employers’ opinion on the question referring to training quality in Moscow higher schools. For this purpose, leading Moscow universities were selected that have the right to form and approve their own educational standards. The study has fixed the positive nature of the most publications in mass-media in relation to the largest Moscow universities. There is positive coverage of university graduates’ employment and adaptation problems. The information reasons were universities activities that contribute to the improvement of the graduates’ competence level. The study has revealed that the problems of evaluation and quality assurance of education are relevant not only for educational organizations, but also for employers. The research has determined that the requirements of the digital society development are such that educational organizations as producers and suppliers of labour should be more result-oriented, and employers should be directly involved in the formation and evaluation of the quality of educational programs. Keywords: digital society, educational organizations, quality of education, employers, social and traditional media. Media messages, specialists, labour market, quality of education, Moscow universities